Computational analysis method of the electromagnetic field propagation and deformation of conductive bodies - Lavinsky, D. V.; Zaitsev, Yu. I. (Національний технічний університет "Харківський політехнічний інститут", 2023)
The electromagnetic field is an integral attribute of the operation of many technical and technological systems. The action of an electromagnetic field leads to deformation, a change in temperature, a change in the physical properties of the materials. Problem. High-intensity electromagnetic fields can cause such a strong deformation of conductive bodies that it can lead to irreversible shape change or destruction. This fact is used in a class of technological operations: electromagnetic forming. Here, both the workpiece and the equipment are subjected to intense force action. As a result, equipment elements may become inoperable. Goal. Creation of a computational analysis method of the electromagnetic field propagation in systems of conductive bodies and subsequent analysis of deformation. Application of this method to the study of processes in electromagnetic forming systems in order to determine rational operational parameters that provide the result of a technological operation. Methodology. A variational formulation of the problems of an electromagnetic field propagation and deformation of conductive bodies systems is used. Numerical modeling and analysis are performed using the finite element method. Results. In a general form, a system of resolving equations for the values of the vector magnetic potential and displacements is obtained. The influence of the electromagnetic field is taken into account by introducing electromagnetic forces. The results of calculations for a technological system designed for electromagnetic forming of curved thinwalled workpieces are presented. Originality. For the first time, a method of computational analysis is presented, which involves modeling within the framework of one design scheme both the process of electromagnetic field propagation and the process of deformation. Practical significance. The proposed method of computational analysis can be used for various technological systems of electromagnetic forming in order to determine the rational parameters that ensure both the operability of the equipment and the purpose of the technological operation - the necessary shaping of the workpiece.

Електромагнітне поле є невід'ємним атрибутом роботи багатьох технічних і технологічних систем. Дія електромагнітного поля призводить до деформації, зміни температури, зміни фізичних властивостей матеріалів. Проблема. Електромагнітні поля високої інтенсивності можуть викликати настільки сильну деформацію провідних тіл, що це може призвести до незворотної зміни форми або руйнування. Цей факт використовується в класі технологічних операцій: електромагнітна обробка. Тут як заготовка, так і обладнання піддаються інтенсивній силовій дії. В результаті елементи обладнання можуть виходити з ладу. Мета. Створення методу розрахункового аналізу поширення електромагнітного поля в системах провідних тіл і подальшого аналізу деформування. Застосування цього методу для дослідження процесів в системах електромагнітної обробки з метою визначення раціональних робочих параметрів, що забезпечують результат технологічної операції. Методологія. Використано варіаційну постановку задач про поширення електромагнітного поля та деформування систем провідних тіл. Чисельне моделювання та аналіз виконано методом скінченних елементів. Результати. У загальному вигляді отримано систему визначальних рівнянь для значень векторного магнітного потенціалу та переміщень. Вплив електромагнітного поля враховується введенням електромагнітних сил. Наведено результати розрахунків для технологічної системи електромагнітної обробки вигнутих тонкостінних заготовок. Оригінальність. Вперше представлено метод розрахункового аналізу, який передбачає моделювання в рамках єдиної розрахункової схеми як процесу поширення електромагнітного поля, так і процесу деформування. Практичне значення. Запропонований метод розрахункового аналізу може бути використаний для різних технологічних систем електромагнітного формування з метою визначення раціональних параметрів, що забезпечують як працездатність обладнання, так і мету технологічноїоперації – необхідне формоутворення заготовки.
Keywords: computational analysis; electromagnetic field; electromagnetic forming; deformation; розрахунковий аналіз; електромагнітне поле; електромагнітна обробка; деформування